Uncommon Presentation of Giant Tophaceous Gout in the Hand: A Case Report - Zmerly, Hassan; Akkawi, Ibrahim; Ruinato, Damiano Alfio; Moscato, Manuela; Draghetti, Maurizio; Pegreffi, Francesco (Current Rheumatology Reviews, 2026)
BackgroundTophaceous gout masses are characterized by the accumulation of monosodium urate crystals in peripheral joints and soft tissues. The most commonly involved areas are the metatarsophalangeal and knee joints. Finger/hand localization is uncommon. If not correctly treated, a finger tophaceous mass can grow and, in rare cases, reach an abnormally large size, termed “giant.”AimThe aim of our study is to present a rare case of a large tophaceous mass of the hand, localized in the fourth finger, and to highlight the role of surgical excision combined with a multidisciplinary team approach.Case ReportWe present a rare case of an 82-year-old woman affected by giant tophaceous gout in the left hand, localized to the extensor region of the proximal interphalangeal joint of the fourth finger. Clinical evaluation, MRI, and ultrasound imaging showed a 35 x 30 mm nodule in the soft tissue.The lesion was successfully treated by mass excision and debridement of the extensor tendon. Histopathologic examination confirmed the diagnosis of tophaceous gout. Post-operatively, a combination of medical and nutritional therapy was given. At a 3-year follow-up, the patient was free of symptoms with no evidence of disease in the fourth finger.ConclusionManagement of giant tophaceous gout in hand necessitates extensive mass excision combined with pharmacological therapy, dietary adjustments, and lifestyle modifications. Effective treatment of such cases requires a multidisciplinary team approach to address the complexity of the condition comprehensively.
Keywords: Gout